Analysis of Work Performance Among Employee-Students Based on Personality Profiles Using the DISC (Dominance, Influence, Steadiness, and Compliance) Test - Sasputri, Aina Zahra Yudiana; Irawan, Tasya Ariadna; Rosida, Zulfa; Puspita, Nindya Dwi; Qatrunnada, Rizqi Zulfa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This research aims to determine the work performance of employees with student status based on personality profiles using the DISC (Dominance, Influence, Steadiness, and Compliance) test. Methodology: This research uses a quantitative method with a descriptive quantitative approach. The research population is active university students working in the Solo Raya area. Sampling using a purposive sampling technique with the criteria of employees with student status, domiciled in Solo Raya, part-time or full-time, and willing to take the test at a location determined by the researcher. Participants who took part in the entire series of tests were 51 people. Data collection used the work performance scale and DISC Psychological Test. Results: Based on data analysis, it is known that the work performance of employees with student status consists of very high (8%), high (14%), moderate (39%), low (35%), and very low (4%) categories. Applications/Originality/Value: This research also concludes that employees with student status have a variety of personality types consisting of dominance, influence, steadiness, compliance, and a combination of them. The implications of this research are discussed further in the research results.